2018
DOI: 10.2108/zs170175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sociosexual Experience and Aging on Number of Courtship Ultrasonic Vocalizations in Male Mice

Abstract: Sexual behaviors are instinctually exhibited without prior training, but they are modulated by experience. One of the precopulatory behaviors in adult male mice, courtship ultrasonic vocalizations (USVs), has attracted considerable academic attention recently. Male mice emit ultrasounds as courtship behavior when encountering females. However, the modulatory effects of experience on USVs remain unclear. In the present study, we aimed to clarify the effects of sociosexual experience and aging on adult male voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Mice. We obtained 10 recording sessions of courtship vocalizations from 6 mice (Mus musculus; C57BL/6J, adult males), under the same condition and recording environment as described in our previous work [38]. Briefly, the microphone was set 16 cm above the floor with a sampling rate of 400 kHz.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice. We obtained 10 recording sessions of courtship vocalizations from 6 mice (Mus musculus; C57BL/6J, adult males), under the same condition and recording environment as described in our previous work [38]. Briefly, the microphone was set 16 cm above the floor with a sampling rate of 400 kHz.…”
Section: Datasetmentioning
confidence: 99%
“…Mouse USVs can be discriminated into several subcategories according to their spectrotemporal patterns [31][32][33][34][35], and these patterns could predict mating success [35,36], though subcategories are not consistent between studies. Their USV patterns are innately acquired rather than a learned behavior [34,37], though sociosexual experience can slightly enhance the vocalization rate [38]. In rat USVs, the pleasant (~50 kHz) and distress (~22 kHz) calls have been suggested to have a communicative function since these calls can transmit the emotional states of the vocalizer to the listener and can modify the listener's behavior such as mating [26,39], approaching [40], or defensive behavior [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether male USV emission influenced male mating success, or vice versa. Second, Kanno and Kikusui [21] recorded males with a novel virgin female both before and after they were housed with another female for 2 weeks. They compared males that emitted USVs with males that did not vocalize before or after co-housing, and they found that vocalizing males sired more offspring than non-vocalizing males during the co-housing phase.…”
Section: Introductionmentioning
confidence: 99%
“…Mice. We obtained 10 recording sessions of courtship vocalizations from 6 mice (Mus musculus; C57BL/6J, adult males), under the same condition and recording environment as described in our previous work (Kanno and Kikusui 2018). In brief, the microphone was set 16 cm above the floor with a sampling rate of 400 kHz.…”
Section: Datasetmentioning
confidence: 99%
“…Mice USV has been suggested to be distinguished into several subcategories according to their spectrotemporal patterns [30][31][32][33][34], and this pattern could predict mating success [34,35], while the subcategories were not well consistent between those studies. Their USV patterns are innately acquired but not learned behavior [33,36], though sociosexual experience can slightly enhance the vocalization rate [37]. In rats USV, the pleasant (~50 kHz) and distress (~22 kHz) calls have been suggested to have a communicative function since these calls can transmit the emotional states of vocalizer to listener and modify listener's behavior such as mating [25,38], approaching [39], or defensive behavior [40,41].…”
Section: Introductionmentioning
confidence: 99%